From the innovation ecosystem in Alagoas to networks of interest IN ST&I: positionings and relations (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
Innovation ecosystems shape agencies of social production of scientific and technological knowledge and local and/or global economic policy. The research aims to map the innovation ecosystem in Alagoas, specifically describing networks of interest that mobilize actors linked to science, technology and innovation. In light of the Actor-Network Theory and the notions of “translation” and “inscription”, semi-structured interviews are used. It presents a chain of common interests of CT&I in Alagoas and society throughout, with the performance of 7 actors who mobilize networks of interest linked to the allocation of public and/or private resources, the execution of scientific and technological projects, the formulation of public policies, maintaining partnerships and compliance and technical-professional training. In addition to a single actor, structure or environment, innovation produces networks of actors whose articulations result in socio-technical and political-economic actions of invention, negotiation and commercialization.
Keywords: innovation; innovation ecosystem; sociology of innovation; interest networks; Alagoas